Factors related to the adoption of organic farming in Spanish olive orchards - Parra Lopez, C.=700 1 Calatrava Requena, J.
(Es, En)
ilus., 34 ref.
Keywords: OLEA EUROPAEA; TECNOLOGIA; INNOVACION; ADOPCION DE INNOVACIONES; AGRICULTURA ALTERNATIVA; ESPAÑA; PRACTICAS ECOLOGICAS